Comparative Drought Tolerance of Two Woody Species - Kaul, O. N.; Kramer, P. J.; Duke, James B. (Indian Forester, 1965)
The drought tolerance of ilex (Ilex cornula var. Burfordii) and azalea (Rhododendron poukhanesis) was compared by measuring transpiration rates, water deficits, and stomatal openings of plants and leaves subjected to water stress. The transpiration rate of uowatered ilex plants declined more rapidly than the transpiration rate of unwatered azalea plants. The water deficit was considerably higher in unwatered azalea plants than in unwatered ilex plants. The stomata closed sooner and at a lower water deficit in ilex than in azalea when subjected to water stress. It is concluded that ilex is more tolerant of drought than azalea because it has more efficient stomatal control of transpiration and a higher redstance to cuticular transpiration.